Energy efficiency of electric scooters in different start modes - Shvetsova Svetlana (E3S Web of Conferences, 2024)
This article examines the energy efficiency of electric scooters in different starting modes. The influence of various start modes on the energy efficiency of electric scooters used in urban environments was analyzed. A comparison was made of the start performance using only the electric battery and the start performance combined with the battery and the physical strength of the electric scooter driver. In this case, the comparison was made with different types of surface on which the launch took place. The results of the analysis of the influence of various start modes on the energy efficiency of electric scooters can be used in research in the field of development of electric transport.